Perspectives from 22 Countries on the legal environment for selection - MYORS, Brett (Institutional Knowledge at Singapore Management University, 2017)
In the United States, the legal context plays a major role in how industrial/organizational (I/O) psychologists approach selection system development. The set of protected groups, the approaches to making an a priori case of discrimination (e.g., differential treatment vs. adverse impact), the key court cases influencing selection, and the prohibitions against preferential treatment (e.g., the 1991 ban on score adjustment or within-group norming) are well known. Selection texts (e.g., Guion, 1998) and human resource management texts (e.g., Cascio & Aguinis, 2008) give prominent treatment to the legal context. In recent years, there has been a growing internationalization of I/O psychology such that psychologists from all over the world work with clients in other countries and contribute to our journals and to our conferences. Test publishers and consulting firms establish offices globally. As this internationalization continues, it becomes increasingly useful to take a broader look at the legal environment for selection, examining similarities and differences in various countries.